Characteristics of Jurassic Source Rocks and Evaluation of Hydrocarbon Resources in Tarim Basin, western China - Liang, Shiqin; Wang, Yuhang; Guo, Yanbo (International Journal of Natural Resources and Environmental Studies, 2024)
Jurassic strata in Tarim are significant for their hydrocarbon-rich content. However, the distribution of hydrocarbon source rocks in this region is uneven, and the conditions for hydrocarbon accumulation vary significantly among the different structural elements. Therefore, it is essential to investigate the distribution of Jurassic source rocks, the evolution history of hydrocarbon generation, and the mechanisms influencing hydrocarbon accumulation for effective hydrocarbon exploration and development. To achieve this, seismic, geologic, drilling, logging, and testing data were integrated to analyze the distribution and quality of hydrocarbon source rocks, the evolution of hydrocarbon generation, and the factors influencing hydrocarbon accumulation in Jurassic hydrocarbon source rocks in Tarim Basin. The study revealed that the Jurassic effective hydrocarbon source rock centers are mainly located in the piedmont areas of Kuqa depression, southwest depression, and southeast depression, as well as Yingjisu sag and Manjiaer sag in the eastern Tarim area. Based on a comprehensive evaluation and comparison of the potential of Jurassic hydrocarbon potential in each secondary structural unit, it is concluded that Kuqa Depression has the most favorable exploration zone due to its excellent hydrocarbon accumulation conditions and abundant hydrocarbon resources. Although the overall exploration potential of the southwest depression is lower than that of the Kuqa depression, the hydrocarbon resources potential of the piedmont thrust belt and the associated depression is very high. Similarly, the eastern part of the Manjiaer sag and the Altun piedmont zone of the southeastern depression still have promising exploration prospects, although the overall exploration potential of the eastern Tarim area and the southeastern depression is not as good as the former two.